Exploring EFL undergraduate students’ academic procrastination in thesis writing: A narrative study in Indonesia - Muslim, Baihaqi Zakaria; Rosida, Emy; Salam, Hamidah; Wardani, Anfi (Journal of Research on English and Language Learning (J-REaLL), 2025)
While a substantial body of literature has investigated the phenomenon of academic procrastination among undergraduate students, research specifically exploring academic procrastination among English as a foreign language (EFL) undergraduate students during thesis writing remains limited. To address this glaring gap, this narrative study aims to gain an in-depth understanding of the interplays of factors contributing to EFL undergraduate students' academic procrastination during their thesis writing process. By employing a purposive sampling technique, this study identified three EFL undergraduate students who volunteered to be involved as research participants. Semi-structured interviews were employed as the primary data collection method to collect the data from participants' live experiences. Through thematic analysis, this study found various factors contributing to EFL students’ thesis writing procrastination, such as learners' inadequate self-regulated capability, language mastery, writing ability, supervisor guidance, and emotional regulation. Additionally, this study also found detrimental effects of thesis writing procrastination on EFL undergraduate students’ wellbeing. By understanding contributing factors and hazardous effects of thesis writing procrastination, this study discussed possible interventions in order to mitigate and overcome thesis writing procrastination among EFL undergraduate students, which ultimately offers implications for future pedagogical practice and research. However, as this study relied solely on interviews for data collection, the findings may not fully reflect the complexity of the issue. Finally, the suggestions and recommendations of this research were also discussed.